Legislative Oversight and Budgeting : A World Perspective - Stapenhurst, Rick (Washington, DC : World Bank, 2012)
Effective legislatures are fundamental to promoting good governance and are a critical component in a country's overall governance framework. Although differences exist across government systems, legislatures, through their constitutional mandates, fulfill three core functions: representation, lawmaking, and oversight. Governance goals of greater accountability, transparency, and participation are directly related to these three functions. Legislative oversight in particular seeks to ensure that the executive and its agencies, or those to whom authority is delegated, remain responsive and accountable. This volume looks at oversight as a continuous and ongoing cycle. Legislatures may examine government policies as they are being developed or work to ensure that programs are implemented and administered efficiently, effectively, and in a manner consistent with legislative intent. In addition, this book highlights the important opportunities provided for oversight during the budget cycle. At the same time, the authors recognize the many factors and incentives legislators face that may assist or impede them in playing their oversight role.